The Effect of Work Environment, Work Stress and Work Motivation on Employee Performance in Freight Forwarding and Logistics Company - I Gede Putu Kawiana; Moh. Samsul Arifin; Daniel Tulasi; Teguh Setiawan Wibowo; Rianti Setyawasih (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to ascertain the impact of work-related stress, motivation, and environment on the productivity of the staff at one of companies that focused on freight forwarding and logistic company. Research of this kind is quantitative. 100 employees made up the study's sample. 80 respondents were used in a random sampling for data gathering. With the use of the SPSS, several linear regression analysis approaches or models are used in this study. The findings of this study suggest that workplace motivation, stress, and surroundings all have an impact on employee performance. Workplace stress has a positive impact on employee performance, employee motivation has a positive impact, and the work environment has a positive impact on employee performance.